Astaxanthin enhances antioxidant capacity to alleviate thermal stress-induced liver inflammation in largemouth bass (Micropterus salmoides): a multi-omics insight into glutathione metabolism remodeling - Sun, Yulong; Zong, Wenzhuo; Wang, Jiteng; He, Jiale; Zhang, Jiankun; Han, Tao (Frontiers in Marine Science, 2025)
Continuing global warming intensifies the thermal stress suffered by fish, urgently necessitating effective mitigating techniques. This study aims to investigate the mechanisms by which astaxanthin alleviates oxidative stress and inflammatory damage induced by thermal stress. Under thermal stress, an increase in oxidative stress was observed in the myocytes of Micropterus salmoides, however, intervention of astaxanthin exerted a notable alleviating effect on oxidative stress. Evidence of thermal stress experiment on primary myocytes indicates that astaxanthin resists thermal stress by enhancing the activity of antioxidant enzymes, heat shock proteins and activating the antioxidant gene Nrf2. Further integrated multi-omics analysis revealed a significant upregulation of several antioxidant biomarkers, such as Glutathione (GSH), glutathione peroxidase (GPX) and glutathione S-transferase (GST). This study proposes the hypothesis that astaxanthin may enhance the GSH-dependent endogenous antioxidant enzyme system by activating the Keap1-Nrf2 signaling pathway. Notably, the supplementation of astaxanthin, compared to thermal stress alone, inhibited the expression of inflammatory factors and apoptosis-related genes, including TLR2, IL8, EIF4E, IL2RB, CASP3, and CASP9. These results, combined with the observed inhibition of the Toll-like receptor signaling pathway and the NF-κB signaling pathway, indicate that the TLR2/4-NF-κB signaling pathway plays a crucial role in mediating the alleviation of oxidative stress-induced inflammatory damage by astaxanthin. Furthermore, astaxanthin remodels amino acid and lipid metabolism under thermal stress, establishing an adaptive anti-thermal stress metabolic mechanism that encompasses both phase I and phase II metabolism. These findings offer novel insights into the mechanisms underlying astaxanthin-induced protection against oxidative stress and inflammatory damage.